Effects of gaseous nitriding AISI 4140 alloy steel on corrosion and hardness properties - Loganathan, Tamil Moli; Wahab, Nor' Aini; Muthaiyah, Gopinathan; Karuppiah, Karmegam; Munusamy, Mmaniyarasi (Institute of Physics Publishing, 2016)
Corrosion is one of the major problems in the industry especially on machinery since it weakens the structure of the machinery part and causes the mechanical failure. This will stop the production and increase the maintenance cost. In this study, the corrosion behaviour of gas nitriding on a screw press machine shaft made from AISI 4140 steel was investigated. Pitting corrosion was identified as a major cause of the shaft failure and this study was conducted to improve the corrosion resistance on the AISI 4140 alloy steel shaft by gas nitriding as a surface hardening treatment. Gas nitriding was performed with composition of 15% ammonia and 85% nitrogen at temperatures of 525 °C, 550 °C and 575 °C and with the soaking time of 30, 45 and 60 minutes, respectively. The samples were prepared as rectangular sized of 30mm x 12mm x 3mm for immersion testing. The results showed that corrosion rate of untreated samples was 77% higher compared to the nitrided samples. It was also found that hardness of the nitrided samples was higher than untreated sample. All in all, it can be concluded that gaseous nitriding can significantly improve the surface hardness and the corrosion resistance of the shaft made of AISI 4140 alloy steel, hence reduces the pitting that is the root cause of failure.